The Development of Human Resources In Islamic Financial Industries From Economic and Islamic Financial Graduates - Nurul Huda; Nova Rini; Desti Anggraini; Khamim Hudori; Yosi Mardoni (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
The purposeof this article is to determine the absorption level of Islamic economics programmegraduates into the Islamic financial industry, in Jakarta and West Java. Thisresearch used exploratory studies method and Alignment Index (AI). The overallresearch results, of 2011 until 2014 graduates showed a low level of absorptioninto Islamic finance industry. Research result showed absorption level in Universityof Muhammadiyah Prof. HAMKA is by 20%, Islamic University 45 bekasiabsoption level continues to increase from year to year, and Juanda UniversityBogor absoption level is below 40%. This occured because the universitiescurriculum is still dominant in the application instead of the application of softskills hardskill.DOI: 10.15408/aiq.v8i1.2512